Understanding Organizational Commitment in Multinational Organizations: The Role of Values, Support, Leadership, and Autonomy - Brucker,Eva (2025)
Organizational Commitment (OC), which describes an individual’s psychological attachment to an organization, is a central component in organizational behavior research. This study examines the impact of perceived organizational values, personal values, organizational support, positive leadership, and job autonomy on OC and its three components: affective, normative, and continuance commitment. Drawing on the Theory of Planned Behavior, this study aims to clarify the relative effects of these predictors by simultaneously including them in multiple regression models. This study analyzed data from 301 employees working in multinational organizations. Therefore, this research additionally contributes to a cross-national perspective on commitment patterns and potential cultural variations in OC. The results indicate that the predictors have distinct effects on OC and its three components. Perceived positive leadership was the most robust predictor of affective, normative, and overall commitment, while perceived organizational support also emerged as a consistent predictor. Among value-based predictors, personal adherence-to-convention and personal and organizational humanity values significantly predicted overall commitment, although their impact varied across commitment components. Additionally, exploratory analyses suggest some cultural and demographic differences in commitment levels, particularly related to power distance, individualism, uncertainty avoidance, organizational tenure, and the frequency of remote work. These findings emphasize the value of viewing OC in its multidimensional form. Understanding the unique antecedents of each commitment dimension can help to drive more targeted strategies within organizations, particularly relevant for multinational organizations that seek to foster specific forms of OC.
Keywords: Organizational Commitment; Organizational Values; Personal Values; Organizational Support; Positive Leadership; Job Autonomy; Three-Component Commitment Model; Theory of Planned Behavior